Energy cooperation between Mongolia and Russia: past, present, and future - Batmunkh, Sereeter; Boris, Saneev; Batkhuyag, Sodov; Ochirbat, Punsalmaa; Tumenjargal, Makhbal; Anatoly, Lagerev; Alexander, Sokolov; Popov, Sergei (Proceedings of the Mongolian Academy of Sciences, 2021)
The paper showcases the experience of energy cooperation between Mongolia and Russia and it gives a brief description of the current state and outlines strategic directions of energy cooperation between the two countries from the perspective of current energy cooperation priorities in the Northeast Asian countries, and active mutually beneficial participation of Mongolia and Russia in this process. Prerequisites for cooperation and conditions for successful intercountry projects in individual industries of the energy sector are considered in the study.